Visual illustration and photography on Islamic book cover designs: a semiotic analysis - Suhaimi, Mohamad Suhaizi; Hashim, Muhammad Faizuddin; Sha'ri, Sharil Nizam (Global Academic Excellence, 2019)
The publication of religious books recently has been in line with the publication of books of other genres. It is because of the increase in the demands by the readers in addition with the design of the book covers which has been made up more interesting. Hence, this research was aimed to identify the influence of visual illustration and photography displayed on book covers which preferred by the readers. Sign theory by Peirce (1839) and Semiotic Analysis by Stokes (2003) were applied for the purpose of data analysis. A book published by Telaga Biru Sdn. Bhd. entitled Ikon Syabab by Umar Muhammad Noor (2014) has been made as the research data focusing on the taxonomy aspect of its cover. The results showed that the proper use of pictures was undeniably able to attract the readers to buy the religious book currently in the market. This research also was predicted to be able to contribute to the national socioeconomic interest, generate a rich cultural society and elevate the percentage of book publication in Malaysia.